Cenopopulations of Adonis wolgensis Stev. in the conditions of Northern Kazakhstan - Sultangazina, G.J.; Steshenko, M.Y.; Novak, Y.O. (Fundamental and Experimental Biology, 2022)
The article presents the study results on the cenopopulations of Adonis wolgensis in Northern Kazakhstan (2019–2021). The materials are obtained as a result of field research; literary data are considered. Based on detailed route studies, the structure of cenopopulations is given. Nine cenopopulations located in the Kostanay region are studied. Populations of A. wolgensis occupy areas from 300 to 1000 m2. The largest total projective cover is noted in forest clearings and along the outskirts of forests. The proportion of A. wolgensis in the total projective cover there is 1–5 %. The studied cenopopulations are characterized by contagious and random types of distribution of individuals in space; a uniform (regular) type is not recorded. An assessment of the vitality type of cenopopulations shows that five of the studied cenopopulations have a normal vitality type and four flourishing ones. Cenopopulations that are in an oppressed, depressed, and infertile states are ot found.